ANALISIS Z-SCORE UNTUK MEMPREDIKSI TINGKAT KEBANGKRUTAN PERUSAHAAN (Studi Pada Industri Farmasi di Bursa Efek Indonesia Periode 2012-2014) - Nurfitriani, Atika Harish (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to determine the level of corporate bankruptcy using model analysis Altman Z-Score on pharmaceutical companies in Indonesia Stock Exchange (IDX) 2012-2014. The study population was all of the Pharmaceutical Industry with a sample of eight pharmaceuticals companies in the Indonesia Stock Exchange (IDX) in accordance with predetermined criteria, namely PT Darya Varis Laboratories Tbk, PT Indofarma (Persero) Tbk, PT Kimia Farma (Persero) Tbk, PT Kalbe Farma Tbk, PT Merck Indonesia Tbk, PT Pyridam Farma Tbk, PT Taisho Pharmaceutical Indonesia Tbk, PT Tempo Scan Pacific Tbk. The analysis technique used is discriminant analysis using variables of the Altman Z-Score. The results of this study indicate that the Altman Z-Score model can be implemented to detect the possibility of bankruptcy in the pharmaceutical company in Indonesia Stock Exchange (IDX). Altman Z-Score model and discriminant analysis do not have the same results in predicting bankruptcy in eight pharmaceutical companies because there is a miss classification in one company out of eight companies. The results of the Z-Score using discriminant analysis is able to classify a pharmaceutical company in two groups, that are healthy and gristle to bankruptcy.Keywords: pharmaceutical company, Bankruptcy Prediction, Altman Z-score model